2019
DOI: 10.1108/ijchm-05-2018-0423
|View full text |Cite
|
Sign up to set email alerts
|

Critical events in the tourism industry: factors affecting the future intention to take a cruise

Abstract: Purpose In recent years, critical events have heavily affected the cruise industry. Such events may variously influence customers’ intention to take a cruise in the future depending on different factors. This paper aims to study such factors, in particular the emotions related to the event, the prior corporate reputation and the use of social media in the corporate communication strategies followed during the crisis. Design/methodology/approach The study is based on the development of a structured questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
(96 reference statements)
1
14
0
Order By: Relevance
“…In terms of the cruise industry, Petrick (2011) argued that corporate reputation is an important concept that strengthens customers' confidence and reduces their risk perceptions (Wu et al, 2018). Penco et al (2019) reported that a prior good reputation mitigates critical events' negative effect on future decisions to cruise by retaining consumers' confidence in the company and its products/services (Souiden and Pons, 2009). Customers with better perceptions of the corporate reputation are therefore, more likely to have favourable behavioural intentions, which mitigate a critical event's effect.…”
Section: Reputationmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the cruise industry, Petrick (2011) argued that corporate reputation is an important concept that strengthens customers' confidence and reduces their risk perceptions (Wu et al, 2018). Penco et al (2019) reported that a prior good reputation mitigates critical events' negative effect on future decisions to cruise by retaining consumers' confidence in the company and its products/services (Souiden and Pons, 2009). Customers with better perceptions of the corporate reputation are therefore, more likely to have favourable behavioural intentions, which mitigate a critical event's effect.…”
Section: Reputationmentioning
confidence: 99%
“…Cruise companies cover all profiles of contemporary hospitality management: marketing strategies, human resource planning and development, operations management, corporate strategies, accounting and communication (Chua et al, 2017;Jones et al, 2017;Penco et al, 2019;Raub and Streit, 2006). Within the hospitality industry, cruising is one of the most susceptible industries to the current COVID-19 health crisis, and therefore, associated with amplified safety and security risks for its passengers and crewmembers (Gössling et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to choose one type of spatial relationship or another is not decisive in the case analysed, although it can be pointed out that in other cases it may be vital. This means that it is recommendable to use several types of spatial relationship and to compare the results, in such a way that the models which are most similar to each other are chosen [25,50,52].…”
Section: Discussionmentioning
confidence: 99%
“…These experiences have a considerable effect on the choice of the final destination by the future tourist and are currently essential for the management of tourist accommodation [19][20][21][22]. Therefore, those with a positive online reputation can increase their prices and maintain their occupation level, while a negative reputation may lead to a drop in the number of tourists [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%